Has Firms' Emphasis on Environmental and Social Sustainability Impacted How They Have Been Affected by and Responded to COVID-19? - Aarstad, Jarle; Jakobsen, Stig-Erik; Fløysand, Arnt (Frontiers in Sustainability, 2022)
This paper’s major focus is to study if firms’ emphasis on environmental and social sustainability has impacted how they have been affected by and responded to covid-19. A survey of Norwegian firms across industries shows that those emphasizing environmental and social sustainability have had a relatively strong response to covid-19, albeit not having been strongly affected. For firms in the aquaculture industry, the results are similar to those emphasizing environmental and social sustainability. Firms in the hospitality, tourism and culture industry and firms with international engagements have been strongly affected by covid-19 and have also had a strong response. Firms with international ownership have been strongly affected but have not had a corresponding response. Overall, being strongly affected by covid-19 does not always result in a corresponding response. Similarly, a strong response to covid-19, being the case for firms emphasizing sustainability, is not always triggered by being strongly affected.